CT-guided transthoracic lung biopsy: Complications and success in yielding a specific diagnosis (Annals of Medical Research, 2023)
Aim: To present risk factors for common complications of CT-guided transthoracic lung biopsy and to analyzing the diagnostic success of the procedure in terms of specific diagnostic rates.Materials and Methods: 461 consecutive procedures retrospectively enrolled. Patient, lesion and technical variables are scrutinized in terms of complications and their severity. Pathology results were evaluated for diagnostic specificity.Results: 27% total complications with 17% alveolar hemorrhage, 7% pneumothorax and 3% developed both. ≤ 15 mm size and ≥ 20 mm distance from pleura significantly increases the risk of both PTX and AH. Perilesional emphysema is a predisposing factor of both severe PTX and extended bleeding. Lateral decubitus position increases the likelihood of pneumothorax. Patients with a needle angle of less than 90±15° had an approximate 2-fold increase risk of PTX (P = 0.034). Semi-solid lesions carry a risk of significant bleeding. The accuracy was 96.9% with a specific malignant diagnosis rate of 83% and a specific benign diagnosis rate of 52%.Conclusion: Perilesional emphysema is risk factor of severe complications. Semi-solid lesions are prone to severe bleeding. Lateral decubitus position and low needle angle are important as preventable predisposing factors of PTX. Although the diagnostic yield is satisfactory, the specific benign diagnosis rates are still below expectations and that larger needle biopsies are more beneficial in this regard.
Keywords: Transthoracic core needle lung biopsy; CT guided lung biopsy complications; Biopsy-induced alveolar hemorrhage; Biopsy-induced pneumothorax